Search for the True Nature of Nucleus-Nucleus Potentials - Islam, M. S.; Tariq, A. S. B.; Joardar, S. K.; Uddin, M. A.; Basak, A. K. (Journal of Scientific Research, 2024)
A review on the research contributions from the nuclear and particle physics laboratory of Rajshahi University is presented. Special emphasis has been given to the nuclear physics research using the molecular nucleus-nucleus (NN) potentials derived from the Pauli-laden energy density functional (EDF) theory. The successes of EDF-derived non-monotonic (NM) NN potentials, compared to other familiar optical model potentials such as Woods-Saxon (WS), Squared Woods-Saxon (SWS), double folding (DF) for NN interactions, have been discussed. The phenomenal successes of NM potentials with a repulsive core have been found to suggest that the true nature of NN potential is NM with the Pauli-compliant EDF as its root.